Biomimicry: A Journey of “Impression de Chaos” / Wan Noor Faaizah Wan Omar and Shafilla Subri - Wan Omar, Wan Noor Faaizah; Subri, Shafilla (Faculty of Art and Design, 2021)
Benyus Jenine coined two Greek words: ‘bio’ meaning life, with ‘mimesis’ meaning imitation. The Biomimicry Approach typically addresses two circumstances, defining a human need or design problem, and identifying ways to resolve challenges faced by other organisms or ecosystems. The three core principles in biomimicry are:nature as a model, nature as a measure, and nature as a mentor. Each principle is explained and responsible for the biomimicry cogitation approach. Nature, as model: Biomimicry is a study of nature's models which produces forms, processes, systems and strategies to resolve human affairs in more sustainable manner. Using nature as a model, the Biomimicry Guild and its collaborators created the Biomimicry Design Spiral as a practical design tool. Nature, as measure: Biomimicry employs an ecological standard to assess the long-term viability of human innovations.